2014
DOI: 10.1166/jpsp.2014.1023
|View full text |Cite
|
Sign up to set email alerts
|

Antidiabetic Activity of <I>Cedrus deodara</I> Aqueous Extract and Its Relationship with Its Antioxidant Properties

Abstract: The present study investigated the antidiabetic potential of Cedrus deodara heart wood aqueous extract and its relationship with its antioxidant properties. Aqueous extract of Cedrus deodara reduces blood sugar level in alloxan induced diabetic rats. Reduction in blood sugar was observed following 5th day onwards after continuous administration of the extract and on 21st day sugar levels were found to be reduced by 40.20%. Oxidative stress produced by alloxan was found to be significantly lowered (P ≤ 0.01) by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…The phytochemical studies on CD have reported that majority of phytoconstituents are present in the wood and needles of CD [ 43 ]. Heartwood and stem bark of CD have been used in experimental animals for evaluating anticancer, analgesic, anti-inflammatory, hypolipidemic, anti-diabetic, gastroprotective and anti-epileptic activities [ 31 , [44] , [45] , [46] ]. In most of the previous experimental studies, the alcoholic extract of either heartwood or stem bark of CD has been used.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The phytochemical studies on CD have reported that majority of phytoconstituents are present in the wood and needles of CD [ 43 ]. Heartwood and stem bark of CD have been used in experimental animals for evaluating anticancer, analgesic, anti-inflammatory, hypolipidemic, anti-diabetic, gastroprotective and anti-epileptic activities [ 31 , [44] , [45] , [46] ]. In most of the previous experimental studies, the alcoholic extract of either heartwood or stem bark of CD has been used.…”
Section: Discussionmentioning
confidence: 99%
“…The dose chosen of the alcoholic extract for evaluating antidepressant effect in rats was 100 mg/kg. This dose was selected from the previous preclinical study which evaluated 3,4-bis(3,4-dimethoxyphenyl) furan-2,5-dione (BDFD) of heart wood in the experimental model of depression [ 24 ] The doses of the aqueous extract in the depression model: 250 and 500 mg/kg were chosen from the experimental study which used the aqueous extract of heartwood of CD in the model of antidiabetic study [ 31 ]. Two doses of the aqueous extract used in mice for testing hypnotic effect were 50 and 100 mg/kg.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…12 The and substantially reduced alloxan-induced oxidative stress and produced a decrease in BGL. 13…”
Section: Devdaru (Cedrus Deodara)mentioning
confidence: 99%
“…In addition, it was also observed that treatment of rats with aqueous wood extract over a study period of 21 days resulted in a dosedependent decrease in TBARS along with restoration of superoxide dismutase (SOD), catalase, glutathione (GSH), and glutathione S-transferase to normal levels. [48] α-amylase inhibitory activity…”
Section: Antidiabetic Activitymentioning
confidence: 99%